Use of environmental scan to assess density, content, and variation of predatory food and beverage marketing in New York City. (July 2022) - Fraser, Katherine Tomaino; Ilieva, Rositsa T.; James, Charita Johnson; Chong, Valerie Peter; Shapiro, Sarah; Willingham, Craig; Roberts, Calpurnyia; Freudenberg, Nicholas
Abstract: To explore the presence of predatory food and beverage marketing in different neighborhoods in New York City (NYC), this study describes the methodology of an outdoor environmental scan of the physical environment. The study was conducted in four NYC neighborhoods over a three-week period, in which pairs of trained researchers canvassed designated neighborhoods to document the presence of food and beverage marketing using photographs taken on digital smart phone devices. Commercial areas in the vicinity of NYC Public Schools and NYC Housing Authority campuses located in four neighborhoods with the highest and lowest nutrition related health indicators were studied: South Bronx, Pelham Throggs Neck, Upper West Side, Chelsea/Greenwich Village. Advertisements were coded against 50+ indicators to quantify pertinent variables including the frequency and content of food and beverages advertised and all forms of predatory marketing observed. Comparisons of prevalence and content of food and beverage advertisements and predatory marketing were made across neighborhoods with the highest and lowest health indicators, using chi-squared analysis, and a significance level of p < 0.05. This article demonstrates a disproportionate presence of predatory marketing in low income NYC neighborhoods with negative health outcomes compared to wealthier neighborhoods. Further, this paper demonstrates the benefits and limitations of using an environmental scan methodology to assess predatory food and beverage marketing in a large urban area such as NYC. Highlights: Predatory marketing describes disproportionately marketing unhealthy food products. Urban built environment influences dietary habits of individuals. Disproportionate presence of predatory food marketing in low income neighborhoods. Benefits, limitations of use of environmental scan to assess predatory marketing. Areas in vicinity of public housing, public school targets for predatory food marketing.